Determinants of Youths Participation in Agribusiness in Akwa Ibom State, Nigeria - Akaninyene, Obot; Essien, Antiaobong; Ejeje, Agube (International Journal of Pure Agricultural Advances, 2022)
Youth involvement in agriculture is beneficial to the economic growth of a nation as it will reduce unemployment and curb crime rate. One sector that has over the years been identified to have the needed capacity to provide employment opportunities to the youth is agriculture but most youth do not have interest in agriculture. Therefore, the study examined the determinants of youth participation in agribusiness in Akwa Ibom State, Nigeria. A total of two hundred and fifty (250) respondents were selected using a multistage sampling technique. The sampling technique used was descriptive and regression analysis. The major constraint identified were lack of initial capital, lack of land, high cost of agricultural inputs, lack of market for agricultural produce, low returns (profit), lack of agribusiness knowledge, poor incentive, lack of access to credit, lack of agricultural insurance, lack of facilities and lack of interest were the identified constraints. In determining what would drive youth into agribusiness, access to agricultural inputs, access to facilities/machineries, access to market for agricultural produce, high returns (profit), incentive, access to credit, availability of land and training on agribusiness were the statistically significant factors that determines the youth participation in agribusiness. The study therefore advised that vocational training should be made compulsory in schools where the young ones are exposed to agriculture as entrepreneur with incentives attached.